2022
DOI: 10.1097/sla.0000000000005697
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Perioperative Chemoprophylaxis in Patients With High Thromboembolic Risk Undergoing Major Abdominal Surgery

Abstract: To determine whether early (before skin closure) versus postoperative chemoprophylaxis affects the incidence of venous thromboembolism (VTE) and bleeding following major abdominal surgery, in a high thromboembolic risk population. Background: Major abdominal surgery incurs both VTE and bleeding risks. Patients with high preoperative VTE risk derive the most benefit from chemoprophylaxis, but carry an increased risk of bleeding. The optimal window for chemoprophylaxis in the perioperative period, whereby both V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The observation that postoperative chemical thromboprophylaxis is associated with a lower risk of bleeding than early usage in antireflux surgery is consistent with studies in gallbladder 9 , liver 17 , ventral hernia 10 , bariatric 18 , breast 19 , hip 20 , and abdominal visceral surgery 8 . Additionally, within major abdominal surgery, subgroup analysis of patients with an inherently high thromboembolic risk also favours postoperative chemical thromboprophylaxis over early usage 21 . These reports, along with findings from two recent meta-analyses, one of randomized trials involving different surgical disciplines 22 , and the other of randomized trials and cohort studies involving major abdominal surgery 23 , demonstrated that postoperative chemical thromboprophylaxis did not diminish protection against VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that postoperative chemical thromboprophylaxis is associated with a lower risk of bleeding than early usage in antireflux surgery is consistent with studies in gallbladder 9 , liver 17 , ventral hernia 10 , bariatric 18 , breast 19 , hip 20 , and abdominal visceral surgery 8 . Additionally, within major abdominal surgery, subgroup analysis of patients with an inherently high thromboembolic risk also favours postoperative chemical thromboprophylaxis over early usage 21 . These reports, along with findings from two recent meta-analyses, one of randomized trials involving different surgical disciplines 22 , and the other of randomized trials and cohort studies involving major abdominal surgery 23 , demonstrated that postoperative chemical thromboprophylaxis did not diminish protection against VTE.…”
Section: Discussionmentioning
confidence: 99%
“…However, these comparisons did not reach statistical significance. Moreover, we recently demonstrated that even in patients with high baseline thromboembolic risk, the timing of perioperative chemoprophylaxis did not impact clinical VTE, but postoperative chemoprophylaxis significantly decreased the risk of bleeding when compared with early chemoprophylaxis 34…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chemoprophylaxis prescription requires balancing the risk of bleeding with thromboembolic protection. Currently, chemoprophylaxis usage is associated with the following issues 3–11 : Guidelines are outdated, unclear or poorly utilized. Compliance is suboptimal, increasing the risk of VTE. The optimal timing of perioperative administration is unclear leading to significant variations in practice. The lack of standardization of chemoprophylaxis may adversely affect bleeding and/or VTE risks. …”
Section: Protecting Paper Year Study Type Operation Participants (N) ...mentioning
confidence: 99%
“…The key findings from these studies are summarized below (Table 1): Chemoprophylaxis administered before skin closure (preoperative and intraoperative initiation) offered no additional protection against VTE but increased the risk of major postoperative bleeding, blood transfusion and re‐intervention, compared to postoperative chemoprophylaxis 4,6–10 In patients with the highest baseline VTE risk, postoperative chemoprophylaxis, compared with its administration before skin closure, was still found to offer equivalent VTE protection whilst reducing the risk of postoperative bleeding 9 Chemoprophylaxis can be safely administered at any time within the first 24 h post‐surgery without adversely affecting VTE and bleeding risks 11 …”
Section: Protecting Paper Year Study Type Operation Participants (N) ...mentioning
confidence: 99%